Precision spectroscopy in astrophysics : proceedings of the ESO/Lisbon/Aveiro Conference held in Aveiro, Portugal, 11-15 September 2006 - Santos, Nuno C. (Springer, 2017)
High-accuracy Doppler shift measurements and high-precision spectroscopy are primary techniques in the search for exo-planets." "Further extremely interesting applications include the analysis of QSO absorption lines to determine the variability of physical constants and the analysis of the isotopic ratios of absorption lines both in stars and in QSOs, and the determination of stellar oscillations through radial velocity measurements. Since the use of high-precision/resolution spectroscopy is closely connected to the ability to collect a large number of photons, the scientific domains using this technique benefit tremendously from the use of 8-meter class telescopes and will fully exploit the tremendous gain provided by future Extremely Large Telescopes (ELTs). IR high-resolution spectroscopy should soon approach the same accuracy regime achieved in the optical range." "This volume covers the astrophysical and technical aspects of high-precision spectroscopy with an outlook to future developments, and represents a reference work for researchers in those fields."--Jacket.